Optimized workflow to minimise intra-fractional motion during stereotactic body radiotherapy of spinal metastases. (December 2022) - vanNiekerk, W.M.; Lazeroms, T.; Rogers, S.J.; Lomax, N.; Hälg, R.A.; Gajdos, V.; Özden, I.; Kessler, E.; Riesterer, O.
Highlights: More frequent mid-treatment image guidance improved accuracy of treatment delivery 97 % of treatment fractions showed an intra-fraction motion of less than 1 mm /1° using mid-arc image guidance Treatment delivery was optimized within a standard treatment timeslot without applying substantial additional radiation dose ExacTrac portal verifications during and between arcs to monitor and correct patient position, limits additional dose to the patient and OAR Abstract: Background and purpose: This study evaluated translational and rotational intra-fractional patient movement during spinal stereotactic body radiotherapy (SBRT) using 6D positioning based on 3D cone beam computerized tomography (CBCT) and stereoscopic kilovoltage imaging (ExacTrac). The aim was to determine whether additional intra-fractional image verification reduced intra-fractional motion without significantly prolonging treatment time, whilst maintaining acceptable imaging related dose. Materials and methods: A retrospective analysis of 38 patients with 41 primary tumour volumes treated with SBRT between September 2018 and May 2021 was performed. Three different image-guided radiotherapy (IGRT) workflows were assessed. The translational and rotational positioning errors for the different imaging workflows, 3D translational vectors and estimates of imaging dose delivered for the different imaging workflows were evaluated. Results: As the frequency of intra-fractional imaging increased from workflow 1 to 3, the mean intra-fraction 3D translational vector improved from 0.91 mm (±0.52 mm), to 0.64 (±0.34 mm). 85 %, 83 % and 97 % of images were within a tolerance of 1 mm/1° for workflows 1, 2 and 3 respectively, based on post treatment CBCT images. The average treatment time for workflow 3 was 13 min, as compared to 12 min for workflows 1 and 2. The effective dose per treatment for IGRT workflows 1, 2 and 3 measured 0.6 mSv, 0.95 mSv and 1.8 mSv respectively. Conclusion: The study demonstrated that the use of additional intra-fractional stereoscopic kilovoltage image-guidance during spinal SBRT, reduced the number of measurements deemed "out of tolerance" and treatment delivery could be optimized within a standard treatment timeslot without applying substantial additional radiation dose.